Glucose handling by hepatocytes from obese Zucker rats. Issue 5 (October 1991) - Carbó, Neus; López-Soriano, Francisco J.; Argilés, Josep M.
Abstract : Hepatocytes isolated from obese Zucker rats showed a significantly higher rate of both [U- 14 C]glucose and [U- 14 C]lactate incorporation into [ 14 C]lipid than those from their lean counterparts. This was associated with a marked increase in the lipogenic rate measured by the incorporation of 3 H2 O into the cell esterified fatty acids. Although there were no changes in the incorporation of the tracer into either [ 14 C]glycogen or 14 CO2, the [ 14 C] total uptake was significantly higher in the obese animals. The high rate of [ 14 C]lipid synthesis from glucose was observed both at 15 and 30 mM substrate concentrations and was linked to an enhanced uptake of the tracer into the cell as measured using the decarboxilation of [1- 14 C]glucose in the presence of phenazine methosulphate. The presence of insulin in the incubation medium had no effect on the uptake of glucose by the liver cells. However, the large uptake of glucose by the hepatocytes from the obese animals was not related to an enhanced rate of transport as measured using 3-O-methyl[U- 14 C]glucose. The activity of glucose-6-phosphate dehydrogenase together with a higher [1- 14 C]glucose/[U- 14 C]glucose descarboxylation ratio indicate a predominant very active pentose phosphate pathway which may be responsible for the enhanced glucose uptake observed in the hepatocytes from the obese animals.